Developing a Teaching Strategy for Mathematical Chemistry Using Maple-Assisted Experimental Data Modelling to Enhance Scientific Reasoning - Deklin Frantius; Liliasari Liliasari (Postgraduate, University of Mataram, 2026)
This study developed a teaching strategy to strengthen scientific reasoning. The study proceeded through preliminary investigation, prototype design, iterative try-outs, and implementation. The preliminary study showed that differential and integral topics in classroom practice remained largely procedural and did not explicitly integrate modelling empirical data. In response, a strategy was designed to connect chemical phenomena, mathematical, and Maple-assisted. Participants were undergraduate students from two universities. Try-out I involved 17 Chemistry students and Try-out II involved 10 Chemistry Education students at university in Palangka Raya, Central Kalimantan, whereas the final implementation involved 30 undergraduate students at university in Bandung, West Java. Comprehension scores increased from 33.22 to 64.88 in Try-out I and from 33.82 to 70.59 in Try-out II. In the final implementation, mean scientific reasoning scores increased from 34.40 to 72.27 for the mathematical aspect and from 31.85 to 70.65 for the chemistry aspect. Gains in scientific reasoning were very strongly correlated with gains in differential–integral understanding (r = 0.969, p < 0.001). These findings indicate that the developed strategy supports scientific reasoning by linking chemical phenomena, mathematical modelling, and Maple. The strategy should be examined in larger samples and other chemistry topics.